O-Alkyl Derivatives of Ferulic and Syringic Acid as Lipophilic Antioxidants: Effect of the Length of the Alkyl Chain on the Improvement of the Thermo-Oxidative Stability of Sunflower Oil - Echeverria-Morgado, J; Forero-Doria, O (Royal Society of Chemistry, 2024)
Lipid oxidation is the major cause of the deterioration of fat-containing foods, especially those containing polyunsaturated fatty acids (PUFAs). Antioxidant additives of synthetic origin are added to matrices rich in PUFAs, such as sunflower oil (SO). However, there is controversy regarding their safety, and their low solubility in both water and fat has led to the search for new covalent modifications through lipophilicity. This work presents the synthesis of O-alkyl acid derivatives from ferulic and syringic acids and the study of their antioxidant capacity and effect on the thermoxidative degradation of SO. Antioxidant activities were evaluated by employing ferric reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays in a concentration range of 10-100 µg mL−1. The IC50 values for DPPH scavenging activity ranged from 15.61-90.43 µg mL−1. The results of the FRAP assay for both O-alkyl ferulic (3a-f) and syringic (5a-f) series revealed a “cut-off” effect on antioxidant activity in carbon five (C5). Thermoxidation study of additives 3b-c and 5b-c showed a decrease in the slope of extinction coefficients K232 and K270 in comparison with SOcontrol. Furthermore, 3c presented higher antioxidant activity than 3b and 1, with a power to decrease the thiobarbituric acid reactive species (TBARS) 6 times higher than SOcontrol at 220 °C. Additives 5b-c exerted a protective effect on the thermoxidation of SO. The results suggest that increasing lipophilic and thermal properties of antioxidants through O-alkyl acid derivatization is an effective strategy for accessing lipophilic antioxidant additives with potential use in food matrices. © 2024 The Royal Society of Chemistry.